Anisotropic charged stellar models in Generalized Tolman IV spacetime - Murad, Mohammad Hassan; Fatema, Saba (© 2015, Società Italiana di Fisica and Springer-Verlag Berlin Heidelberg, 2016)
This article was published in the Journal of European Physical Journal Plus [© 2015, Società Italiana di Fisica and Springer-Verlag Berlin Heidelberg.] and the definite version is available at : http://dx.doi.org/10.1140/epjp/i2015-15003-y. The Journal's website is at: http://link.springer.com/article/10.1140%2Fepjp%2Fi2015-15003-y